Geographical context in plant breeding priorities – groundnuts in West and Southern Africa - Mbugua-Gitonga, Agnes; Rutsaert, Pieter; Kitoto, Victor; Khaemba, Colleta (2024)
The study explores the significance of geographical context in setting plant breeding priorities. Historically general geographical considerations like climatic conditions have taken centre stage in plant breeding ensuring design and release of varieties that are well suited to grow in each region with the aim of achieving optimal yields while prioritizing traits that cater for biotic and abiotic stress as well as maturity suitability. The result of this has been varieties with pest and disease resistance packs, yield optimization and right maturity for specific geographical regions. This has largely taken care of a farmers’ agronomic needs. However, an easy to grow crop is not all that is required to drive variety adoption within geographical context. There are also unique end use considerations to be considered in geographical context. Within geographical context, the use of any crop is influenced by several factors. Historical production and consumption context plays a critical role, for example in Nigeria ground nut was grown for both local and export market. With challenges that faced the export market local market became the focus. Therefore, export market requirements and specifications are no longer a key focus in Nigeria. In this market, the big question then becomes what the main local uses are and what this means for trait prioritisation. The role of the crop in the household is another driver within geographical context, is the crop used as a main component in the diet of the farming community? Are there multiple uses that would require unique trait consideration for identified uses? The crop may also play a critical role in cultural and religious ceremonies with specific requirement that need to be put into consideration in choosing the right variety suitable for each region. On the other hand, Malawi market has different requirements as it focuses on export market. From the study, it was established both countries have different trait requirement driven the different end uses.